2018
DOI: 10.4992/jjpsy.88.16347
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the Social Value Orientation on judging trustworthiness and gathering information on character

Abstract: The Social Value Orientation (SVO) explains individual differences in cooperation attitudes. In this study, we examine whether the SVO affects the time taken, and amount of information gathered, when judging the trustworthiness of other people. Participants were able to choose a partner based on the past allocation patterns of candidates, mimicking how people are able to select with whom they cooperate in their social environments. We investigated the effect of the SVO on the method of gathering information on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…24 It has also been indicated that affiliative motivation is associated with prosocial behavior and cooperative behavior, and achievement motivation is associated with aggression. [25][26][27][28] Based on these findings in the field of psychology, we adopted four search terms related to interaction: communication, conversation, self-disclosure, and emotional processing. Additionally, trust, prosocial behavior, cooperative behavior, and aggression were adopted as search terms related to interpersonal behavior.…”
Section: Literature Review Methods 21 Interpersonal Cognition/behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…24 It has also been indicated that affiliative motivation is associated with prosocial behavior and cooperative behavior, and achievement motivation is associated with aggression. [25][26][27][28] Based on these findings in the field of psychology, we adopted four search terms related to interaction: communication, conversation, self-disclosure, and emotional processing. Additionally, trust, prosocial behavior, cooperative behavior, and aggression were adopted as search terms related to interpersonal behavior.…”
Section: Literature Review Methods 21 Interpersonal Cognition/behaviormentioning
confidence: 99%
“…At this time, when based on affiliative motivation, emotional ties are established and maintained (trust), and when based on achievement motivation, competitive behavior, such as outdoing others, occurs 24 . It has also been indicated that affiliative motivation is associated with prosocial behavior and cooperative behavior, and achievement motivation is associated with aggression 25–28 . Based on these findings in the field of psychology, we adopted four search terms related to interaction: communication, conversation, self‐disclosure, and emotional processing.…”
Section: Literature Review Methodsmentioning
confidence: 99%